Fixed Point Results for Generalized Fuzzy Contractive Mappings in Fuzzy Metric Spaces with Application in Integral Equations. (17th May 2021) - Mohammadi, Babak; Hussain, Azhar; Parvaneh, Vahid; Saleem, Naeem; Shahkoohi, Rogheieh Jalal
Abstract : In this paper, we introduce generalized α -η -fuzzy contractive mappings and generalized β -ζ -fuzzy contractive mappings and prove existence of fixed point for such mappings. Our results generalize and improve the recent work of Gopal and Vetro (Iranian journal of fuzzy systems, 11 (2014), 95–107). Some equivalent conditions of our results are presented. Also, an example is given to support our new results.